An Investigation on the Antibacterial and Antibiofilm Efficacy of a Traditional Thai Herbal Recipe (THR 01) against Clinical Isolates of Methicillin Resistant Staphylococcus Aureus (MRSA) and Staphylococcus epidermidis - Loahaprapanon, S.; Yincharoen, K.; Nukong, J.; Chanwun, T. (International Journal of Agricultural Technology, 2018)
Natural compound from herbal medicine are important for the source of drug discovery and in this study selected on the basis of folklore medicinal reports practiced in Thung Song district, Nakhon Si Thammarat province, southern of Thailand. This study reports about at investigating the effect of six ethanolic extracts from traditional Thai herbal recipe (THR 01) and it components, Ocimum sanctum, Rhinacanthus nasutus, Quisqualis indica, Vitex glabrata and Stemona tuberosa against clinical isolates of methicillin resistant Staphylococcus aureus (MRSA) NPRC S001-S005, Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 35984 by broth microdilution method. The results indicated that ethanolic extracts of S. tuberosa showed strong antibacterial activity against S. aureus ATCC 25923 and S. epidermidis ATCC 35984 were 250 µg/ML in both bacteria tested. The biofilm inhibitory concentration of 500-1,000 µg/ML of ethanolic extracts were found to be significant, the most efficiency extracts is S. tuberosa as compared to other ethanolic extracts. The experiment was conducted at the laboratory of Science and Technology Faculty, Rajamangala University of Technology Srivijaya, Nakhon Si Thammarat Campus during October, 2016 to Desember, 2017. However, this study also required test in vivo and toxicity for develop Thai herbal in the further.